1999
DOI: 10.1063/1.124605
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a single freestanding multiwall carbon nanotube on each nanonickel dot

Abstract: Patterned growth of freestanding carbon nanotube͑s͒ on submicron nickel dot͑s͒ on silicon has been achieved by plasma-enhanced-hot-filament-chemical-vapor deposition ͑PE-HF-CVD͒. A thin film nickel grid was fabricated on a silicon wafer by standard microlithographic techniques, and the PE-HF-CVD was done using acetylene (C 2 H 2 ) gas as the carbon source and ammonia (NH 3 ) as a catalyst and dilution gas. Well separated, single carbon nanotubes were observed to grow on the grid. The structures had rounded bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
196
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(204 citation statements)
references
References 18 publications
2
196
0
2
Order By: Relevance
“…It was found that reduction gases such as H 2 and NH 3 were not necessary for carbon nanotube formation during PECVD compared to thermal CVD. In thermal CVD, CH 4 does not dissociate in the gas phase and the nanotube production is entirely due to the surface reaction of CH 4 on the catalyst surface. With no H 2 or NH 3 added, catalyst particles would keep oxidation or be poisoned due to the deposition of amorphous carbon, resulting in a poor growth of CNTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that reduction gases such as H 2 and NH 3 were not necessary for carbon nanotube formation during PECVD compared to thermal CVD. In thermal CVD, CH 4 does not dissociate in the gas phase and the nanotube production is entirely due to the surface reaction of CH 4 on the catalyst surface. With no H 2 or NH 3 added, catalyst particles would keep oxidation or be poisoned due to the deposition of amorphous carbon, resulting in a poor growth of CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma enhanced CVD (PECVD) has been recognized as one of the viable fabrication techniques of carbon nanotubes (CNTs) to produce vertically aligned nanotubes on patterned substrates at relatively low temperature [1][2][3][4]. A variety of plasma reactors have been used to grow carbon nanotubes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…over a catalyst containing nanoparticles of transition metal (Fe, Co, Ni) or of the related oxide, embedded in solid matrices or supported on the surfaces of porous materials in a temperature range of 3001200°C. Good alignment 12) as well as positional control on a nanometric scale 13) can be achieved by using this method. In addition, this synthesis technique also has the advantage of control over the diameter, shell number, and growth rate of CNTs by altering the size of the nanoparticles and the deposition conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of individual and multiple vertically aligned carbon nanofibres can be directed by traditional lithographic methods allowing for accurate positioning of carbon nanofibres across spatial dimensions ranging from nanometres to centimetres [7]. Further, manipulation of the growth process can be used to control the length, shape, and vertical alignment of the nanofibres [8,9]. This control over synthesis at the nanoscale can be combined with conventional micromachining techniques for both top-down and bottom-up fabrication of complex structures.…”
Section: Introductionmentioning
confidence: 99%